Disentangling quality and safety indicator data: a longitudinal, comparative study of hand hygiene compliance and accreditation outcomes in 96 Australian hospitals. Issue 9 (23rd September 2014) - Mumford, Virginia; Greenfield, David; Hogden, Anne; Debono, Deborah; Gospodarevskaya, Elena; Forde, Kevin; Westbrook, Johanna; Braithwaite, Jeffrey
Abstract : Objectives: The study aims are twofold. First, to investigate the suitability of hand hygiene as an indicator of accreditation outcomes and, second, to test the hypothesis that hospitals with better accreditation outcomes achieve higher hand hygiene compliance rates. Design: A retrospective, longitudinal, multisite comparative survey. Setting: Acute public hospitals in New South Wales, Australia. Participants: 96 acute hospitals with accreditation survey results from two surveys during 2009–2012 and submitted data for more than four hand hygiene audits between 2010 and 2013. Outcomes: Our primary outcome comprised observational hand hygiene compliance data from eight audits during 2010–2013. The explanatory variables in our multilevel regression model included: accreditation outcomes and scores for the infection control standard; timing of the surveys; and hospital size and activity. Results: Average hand hygiene compliance rates increased from 67.7% to 80.3% during the study period (2010–2013), with 46.7% of hospitals achieving target compliance rates of 70% in audit 1, versus 92.3% in audit 8. Average hand hygiene rates at small hospitals were 7.8 percentage points (pp) higher than those at the largest hospitals (p<0.05). The association between hand hygiene rates, accreditation outcomes and infection control scores is less clear. Conclusions: Our results indicate that accreditation outcomes and hand hygiene audit data are measuring different parts of the quality and safety spectrum. Understanding what is being measured when selecting indicators to assess the impact of accreditation is critical as focusing on accreditation results would discount successful hand hygiene implementation by smaller hospitals. Conversely, relying on hand hygiene results would discount the infection control related research and leadership investment by larger hospitals. Our hypothesis appears to be confounded by an accreditation programme that makes it more difficult for smaller hospitals to achieve high infection control scores.